2019
DOI: 10.1016/j.engfracmech.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling progressive failure in multi-phase materials using a phase field method

Abstract: In this paper, a new phase field method is proposed for modelling of progressive failure in multi-phase materials. Material properties of the interface between inclusion and matrix are regularized by an auxiliary interface phase field. In addition, crack initiation and propagation are simulated by using another crack phase field. Different failure mechanisms such as interface debonding, matrix cracking and the interaction between these two failure mechanisms are modelled in a unified framework. For general app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 75 publications
(129 reference statements)
1
22
0
Order By: Relevance
“…From these results it is observed that the crack nucleates from the interface and then kinks into the matrix when reaching a certain point. This leads to the final predicted semi-debonding angle of 65.10 • which is similar to the quasi brittle cases [73,74]. The difference compared with similar cases but involving a quasi brittle matrix [53,74] is that the initial interface debonding position in this model is about 45 • direction in the fiber surface (see Fig.…”
Section: Traction Test Of a Microstructure With A Single Fibersupporting
confidence: 57%
“…From these results it is observed that the crack nucleates from the interface and then kinks into the matrix when reaching a certain point. This leads to the final predicted semi-debonding angle of 65.10 • which is similar to the quasi brittle cases [73,74]. The difference compared with similar cases but involving a quasi brittle matrix [53,74] is that the initial interface debonding position in this model is about 45 • direction in the fiber surface (see Fig.…”
Section: Traction Test Of a Microstructure With A Single Fibersupporting
confidence: 57%
“…In the previous study, 53 the authors have proposed an interface regularization scheme to eliminate the material heterogeneity by introducing an auxiliary phase field termed as the interface phase field (IPF). The previous regularization theory was proposed mostly for concrete or materials in which the shape of the inclusion could be arbitrary.…”
Section: An Auxiliary Phase Field For Fiber-matrix Interfacementioning
confidence: 99%
“…In the previous study, 53 the distribution of g is obtained through solving the finite element equation. For this purpose, one has to set the value of g to be 1 to satisfy the Dirichlet boundary condition.…”
Section: Generation Of the Local Microscopic Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, by analogy to the phase field method, the interface was regularised throughout the whole computation domain according to a level set function. This idea of interface regularisation was also incorporated by Zhang et al [11] based on the unified phase field model of [7] for cohesive fracture problems. Hansen-Dörr et al [12] proposed a phase field model, in which the adhesive interface is assigned a fracture toughness within a finite width.…”
Section: Introductionmentioning
confidence: 99%